Development of Biology Teaching Materials Based on Biopreneurship for High School Students - Hasanah, Nur; Jufri, A. Wahab; Japa, Lalu (Jurnal Pijar Mipa, 2025)
Biology learning in high school often faces challenges due to students’ reliance on teacher explanations and conventional textbooks, which tend to be less engaging and limit the development of critical and entrepreneurial skills. To address this issue, innovative teaching materials are needed that not only improve students’ understanding of biological concepts but also foster creativity and independence through entrepreneurship-based approaches. This study aims to develop and test the validity of biopreneurship-based biology teaching materials for high school students. The research employed a 4D development model (Define, Design, Develop, and Disseminate) with a focus on the first three stages. Validation of the teaching materials was conducted by three expert validators using questionnaires, and the results were analyzed with the Aiken index. The construct validity assessment produced values ranging from 0.58 to 0.94, while content validity ranged from 0.63 to 0.75, both categorized as valid. Additionally, the readability test using the Flesch-Kincaid Grade Level showed that most of the text fell within the easy-to-moderate range, making it suitable for high school students. These findings indicate that the developed materials meet the scientific and pedagogical standards required for classroom use. Furthermore, the integration of biopreneurship elements into the biology content provides an innovative approach that not only enhances students’ conceptual understanding but also motivates them to develop an entrepreneurial spirit, particularly in managing biological resources. Overall, this study concludes that the developed teaching materials are valid, relevant, and beneficial for high school biology learning, making biology both meaningful and applicable to students’ real-life contexts.